METHODOLOGICAL ASPECTS OF COMBINED USE OF REHABILITATION MEASURES IN THE RECOVERY OF POSTOPERATIVE MENISCI - Shpekht M. V. (Žurnal Grodnenskogo Gosudarstvennogo Medicinskogo Universiteta, 2020)
Background. The damage of the meniscus of the knee joint leads to its blocking and is accompanied by the phenomenon of synovitis, deforming arthrosis and involvement in the pathological process of previously intact structures. There is a need to optimize surgical treatment of knee injuries and as a result – to search for new effective methods of rehabilitation. Objective. To develop a method of combined application of interval vacuum therapy (IVT) and kinesiotaping, as well as to study its effect on the recovery time of postoperative menisci in athletes. Material and methods. The Vacusport device and kinesiotapes were chosen to develop a new method of rehabilitation. Two groups of athletes were formed: a control group (n=21) and an experimental group (n=21). Goniometryynamometry, linear measurements, and motor tests were chosen as research methods. Cortisol, testosterone, and indicator enzymes creatine kinase (СК) and lactate dehydrogenase (LDH) levels were tested in serum during the postloading period. Results. After two weeks of using the combined method, the experimental and control groups had statistically signifcant differences in the "bending angle" indicator (p=0.034; W=137), and two weeks later, differences were amplifed (p=0.0003; W=78.5 and p=0.0001; W=71, respectively). It was found that the experimental and control groups had no statistically signifcant differences over the entire time interval in terms of «hip circumference». Comparisons of the distributions of the indicators «strength test», «pain», «edema» showed that there were statistically signifcant differences in all the studied parameters after the second week of using the combined method («strength test» − at p=0.0307, «pain» − at p=0.019, «edema» - at p=0.0084). The change in the concentration of cortisol and testosterone hormones and the activity of CK and LDH in the blood serum showed stabilization of cortisol levels, as well as favorable dynamics of CК and LDH activity. Conclusions. The combined use of IVT and kinesiotherapy in a complex of rehabilitation events in athletes after surgical treatment can reduce the recovery time at the initial (sparing) stage.